Plan de marketing para la sucursal del Comisariato Don Paco en la Ciudad de Chone. - Espinoza Rodríguez, Jelixa Lisbeth (2018)
The present investigation was developed in Don Paco store, branch in Chone canton, with the purpose to offer a marketing plan that allows the company to position itself in the competitive market, focusing on knowing the wishes and needs of its clients. As a result of an increase in sales and therefore a higher profitability in the income of the same, is why techniques such as interview and survey were used, which helped to know the current situation of the business and in turn identify which were the segments that required such attention in the sector, to cover those spaces in the market that were not being served. Likewise, the Microsoft Excel tool was used to represent, through graphs, the percentages obtained in the market study, data that were derived from the survey of 385 people who buy in supermarkets. On the other hand, it is worth noting that in the development of this research, three phases were carried out that complied with the specific objectives of the study, detailing through activities what was achieved. In addition to helping direct the commercial strategies used in the combined matrix for a marketing plan that promotes the acquisition of new customers, which in turn generated the realization of an action plan through the matrix 5W + 1H, which allowed tracking to the execution of the proposed strategies and find solutions for the problems encountered.